35TiPRibociclib plus goserelin with hormonal therapy versus physician choice chemotherapy in pre-/perimenopausal patients with HR+, HER2– inoperable locally advanced breast cancer (ABC): RIGHT choice study. (24th November 2019) - Lu, Y-S; Malwinder, S S; Azim, H; Eralp, Y; Im, S-A; Yap, Y S; Alfaro, T Delgar; Gao, M; Saghir, N S El
Abstract: Background: Approximately half of all patients (pts) with breast cancer in Asia-Pacific (∼42%) and the Middle East (∼50%) are under 50 years of age. In routine clinical practice, a substantial proportion of women aged <50 years with endocrine-responsive ABC are initially treated with cytotoxic chemotherapy (CT). Phase 3 trials have shown higher response rates and longer progression-free survival (PFS) and overall survival with endocrine therapy (ET) plus a cyclin-dependent kinase (CDK) 4/6 inhibitor than with ET monotherapy; however, clinical trials in pre-/perimenopausal pts with ABC are needed to assess the efficacy of ET plus a CDK4/6 inhibitor versus CT when CT is considered. Trial design: The RIGHT choice study is a randomized, open-label phase II study aiming to enroll 222 pre-/ perimenopausal women aged 18–59 years with hormone receptor-positive (HR+), human epidermal growth factor receptor-2-negative (HER2–) ABC across 58 sites in 13 Asian/Middle Eastern countries and Russia (11 enrolled as of June 13, 2019). Pts must have advanced disease not amenable to curative therapy, with symptomatic visceral metastases or impending visceral compromise, rapid disease progression, or markedly symptomatic nonvisceral disease for which combination CT is usually indicated. Pts must have had no prior systemic ET or CT for advanced disease except luteinizing hormone-releasing hormone agonist, and have an ECOG performance score ≤2. Tumors must be estrogen receptor-positive in ≥ 10% of cells or have an Allred score ≥5, per local laboratory testing. Postmenopausal, pregnant, or lactating women will not be included. Pts will be randomized to either 600 mg ribociclib (3 wks on/1 wk off) plus goserelin and letrozole or anastrozole, or to investigator's choice of docetaxel + capecitabine, paclitaxel + gemcitabine, or capecitabine + vinorelbine. The primary endpoint is PFS. Secondary endpoints include time to treatment failure, overall response rate, clinical benefit rate, time to response, overall survival, patient-reported outcomes, and safety. Healthcare resource utilization will be an exploratory endpoint. Clinical trial identification: NCT03839823. Legal entity responsible for the study: Novartis Pharmaceuticals Corporation. Funding: Novartis Pharmaceuticals Corporation. Disclosure: Y-S. Lu: Advisory / Consultancy, Speaker Bureau / Expert testimony: Eli Lilly; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self), Research grant / Funding (institution): Novartis; Advisory / Consultancy, Speaker Bureau / Expert testimony: Pfizer; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self), Research grant / Funding (institution): Roche; Speaker Bureau / Expert testimony: Elsai; Speaker Bureau / Expert testimony: EuroPharma; Speaker Bureau / Expert testimony, Research grant / Funding (self), Research grant / Funding (institution): Merck; Research grant / Funding (institution): Daiichi Sankyo; Research grant / Funding (institution): Odonate. S.S. Malwinder: Speaker Bureau / Expert testimony, Research grant / Funding (self): AstraZeneca; Speaker Bureau / Expert testimony: Eli Lilly; Speaker Bureau / Expert testimony: Merck; Speaker Bureau / Expert testimony, Research grant / Funding (self): Novartis; Speaker Bureau / Expert testimony: Pfizer; Research grant / Funding (self): Asian Pharmaceuticals; Leadership role: Malaysian Oncology Society. H. Azim: Advisory / Consultancy, Speaker Bureau / Expert testimony: Amgen; Advisory / Consultancy, Speaker Bureau / Expert testimony: AstraZeneca; Advisory / Consultancy, Speaker Bureau / Expert testimony: Bristol-Myers Squibb; Advisory / Consultancy, Speaker Bureau / Expert testimony: Eli Lilly; Advisory / Consultancy, Speaker Bureau / Expert testimony: Merck; Advisory / Consultancy, Speaker Bureau / Expert testimony: Novartis; Advisory / Consultancy, Speaker Bureau / Expert testimony: Pfizer; Advisory / Consultancy, Speaker Bureau / Expert testimony: Roche; Advisory / Consultancy, Speaker Bureau / Expert testimony: Janssen; Advisory / Consultancy: Hekma; Advisory / Consultancy: Bayer. Y. Eralp: Advisory / Consultancy, Research grant / Funding (institution): Merck; Advisory / Consultancy, Research grant / Funding (institution): Novartis; Advisory / Consultancy: Pfizer; Advisory / Consultancy, Speaker Bureau / Expert testimony: Roche; Advisory / Consultancy, Speaker Bureau / Expert testimony: Bristol-Myers Squibb; Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy: Nobel. S-A. Im: Advisory / Consultancy, Research grant / Funding (self), Travel / Accommodation / Expenses: AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Novartis; Advisory / Consultancy: Roche; Advisory / Consultancy, Research grant / Funding (self): Pfizer; Advisory / Consultancy: Amgen; Advisory / Consultancy: Elsai; Advisory / Consultancy: Hanmi. Y.S. Yap: Honoraria (self), Travel / Accommodation / Expenses: AstraZeneca; Honoraria (self), Travel / Accommodation / Expenses: Eisai; Honoraria (self), Travel / Accommodation / Expenses: Eli Lilly; Honoraria (self), Travel / Accommodation / Expenses: Novartis; Honoraria (self), Travel / Accommodation / Expenses: Pfizer; Honoraria (self), Travel / Accommodation / Expenses: Roche. T. Delgar Alfaro: Full / Part-time employment: Novartis. M. Gao: Full / Part-time employment: Novartis. N.S. El Saghir: Honoraria (self): Eli Lilly; Honoraria (self): Novartis; Honoraria (self): Pfizer; Honoraria (self): Roche.